Pengembangan Aplikasi Sistem Informasi Persediaan Barang Menggunakan Model Waterfall - Saifudin, Aries; Saputra, Andi Kusuma; Saputra, Bagas; Subhan, Fajrial; Maulana, Fiqri Nanda; Kusyadi, Irpan (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
In an enterprise, the inventory system is a very important aspect for the inventory needs to be used by the company. From the results of research that has been carried out by group 7, material inventory inspections are carried out manually, so that from these problems an information technology is needed for the inspection of a supply. In developing an inventory information technology, we will use the waterfall method. In the results of the experiment, it was found that the waterfall model can be developed to build an inventory information technology system that can improve employee performance and make it easier for companies to help companies to increase sales. To find out whether or not an application is feasible to conduct a feasibility test on a company using ISO 9145-3 and the results of the evaluation are obtained, Ease of learning by 78%, Ease of accessing programs by 85% and suitability in goals by 89%, ease of understanding by 83%